The theory and practice of Reverse Logistics. Issue 1 (17th January 2007) - Meade, Laura; Sarkis, Joseph; Presley, Adrien
This paper provides a review of the literature on Reverse Logistics (RL). It provides an overview of definitions, research and research opportunities in this field. It is a timely and important concept with significant international research under completion at this time. Ample opportunities exist for the growth of this field due to its multi-functional, and interdisciplinary focus. It also is critical for organisations to consider from both an economic and environmental perspective. All these issues are discussed and summarised in this paper.